2006
DOI: 10.1093/gerona/61.10.995
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Disorganization of the Excitation-Contraction Coupling Apparatus in Aging Human Skeletal Muscle as Revealed by Electron Microscopy: A Possible Role in the Decline of Muscle Performance

Abstract: An impairment of the mechanisms controlling the release of calcium from internal stores (excitation-contraction [EC] coupling) has been proposed to contribute to the age-related decline of muscle performance that accompanies aging (EC uncoupling theory). EC coupling in muscle fibers occurs at the junctions between sarcoplasmic reticulum and transverse tubules, in structures called calcium release units (CRUs). We studied the frequency, cellular localization, and ultrastructure of CRUs in human muscle biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 61 publications
12
74
2
1
Order By: Relevance
“…We have already demonstrated that in adult muscle fibers of elderly there are alterations of CRU (Boncompagni et al, 2006). Sarcopenia is characterized by progressive denervation with loss of motor units (McNeil et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We have already demonstrated that in adult muscle fibers of elderly there are alterations of CRU (Boncompagni et al, 2006). Sarcopenia is characterized by progressive denervation with loss of motor units (McNeil et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the tubular aggregates, the extent of these defects correspond with the size of the uncoupled Ca 2+ pool in a given muscle type. Additionally, electron microscopy studies of aged human muscle revealed similar disruptions of the triad junctions, but not an increased presence of large tubular aggregates (Boncompagni et al, 2006). Thus, it is likely that one factor contributing to the compromised Ca 2+ spark signaling in aged skeletal muscle may originate from the disruption of the connection between the t-tubule and SR membrane surfaces.…”
Section: Alteration Of Intracellular Membrane Ultrastructure During Mmentioning
confidence: 92%
“…Interestingly, some of these ultrastructural defects were also observed in aged wild type muscle, raising the possibility that defective membrane integrity or membrane cross-talk may be partially responsible for defects associated with aging (Boncompagni et al, 2006;Weisleder et al, 2006).…”
Section: Mg29 As a Marker Of Age-related Dysfunction In Skeletal Musclementioning
confidence: 99%
“…7 Some peculiar features allowed us to clearly distinguish large striated fibers in our patients from fibers of controls. 25 The myofibrillar apparatus, while quite well preserved, is in general less ordered than in normal muscle (Figure 5c, black arrows). In addition, large and abnormal areas filled with glycogen granules, mitochondria and vesicles were also frequent (Figures 5c and 6a, empty arrows).…”
Section: Force Measurementmentioning
confidence: 96%
“…[23][24][25] The contractile apparatus, formed by long cylinders called myofibrils, is formed by basic elements, the sarcomeres, which are delimited by Z lines (Figure 5a, black arrows). Sarcomeres of adjacent myofibrils are usually quite well aligned, forming the dark-pale cross striation that characterizes skeletal muscle.…”
Section: Force Measurementmentioning
confidence: 99%